COMPORTAMIENTO ASINTÓTICO DE LA ECUACIÓN DE ONDA CON CONDICIÓN DE FRONTERA TIPO NEUMANN, LOCALMENTE DISTRIBUIDA - Pérez Salvatierra, Alfonso (2006)
In the system (*), with Neumann boundary conditions and locally distributed dissipation; where a (x) ≥ a0 >0 a.e.in ω, ωΩ neighborhood 0f Γ= ∂Ω which is an open problem, see [6], we study the asymptotic behavior.